2011
DOI: 10.1007/s00268-011-1386-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seat Belt Usage on Injury Pattern and Outcome of Vehicle Occupants After Road Traffic Collisions: Prospective Study

Abstract: Seat belt usage reduces the severity of injury, hospital stay, and number of operations in injured patients. Seat belt compliance is low in our community. More legal enforcement of seat belt usage is mandatory to reduce the severity of injury caused by RTCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 27 publications
6
63
4
4
Order By: Relevance
“…[6] Vehicle occupants not wearing seatbelts are generally young, male, and have poor driving habits (driving under the influence of alcohol, speeding, previous road traffic collisions and driving offences). [6][7][8][9] We also found that seatbelt use decreased dramatically during night-time driving (Fig. 2), but this trend is also not unique to Cape Town.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…[6] Vehicle occupants not wearing seatbelts are generally young, male, and have poor driving habits (driving under the influence of alcohol, speeding, previous road traffic collisions and driving offences). [6][7][8][9] We also found that seatbelt use decreased dramatically during night-time driving (Fig. 2), but this trend is also not unique to Cape Town.…”
Section: Discussionmentioning
confidence: 65%
“…[12] Multiple studies have highlighted the association between seatbelt non-compliance and injury severity, mortality, and disposition from the emergency centre or trauma unit. [6,8,13,14] In a prospective study (N=766) in the United Arab Emirates, belted occupants had a lower mean ISS (6.1 v. 9.4; p=0.001), a shorter hospital stay (5.3 v. 9.6 days; p=0.005) and a lower mortality rate (1.5% v. 2.4%; p=0.075). [8] A study in the USA (N=23 920) evaluated the Wisconsin Crash Outcome Data Evaluation System (CODES) database and found that admission rates were twice as high and mortality rates three times higher in the unbelted group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique case number was used to identify each patient and the data entered into the database was anonymous. The patients of the present study are a subset of the cohort used for previously published research into other elements of the injuries sustained in road traffic collisions 7 . This study was approved by The Local Ethics Committee of Al-Ain Health district area (RECA/02/44) and was performed in accordance with the ethical standards laid down in the 1964 Declaration of Helsinki and its later amendments.…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al reported that restrained occupants who sustained an injury to the knee, thigh or hip were four times less likely to suffer from a serious intra-abdominal injury in a frontal-impact road traffic collision 6 . Although the advantages of the safety belt are well-established 7,8 , the relationship between lower limb injuries and other body regions is less well understood.…”
mentioning
confidence: 99%